SC20 Simulation – an under-utilised method of education for renal nurses?. (November 2018) - Feneley, Andrew; Jenkins, Karen; Swanborough, Helen; Debling, Paula; Adams, Anthony; Featherstone, Barry
Abstract : Background: Kent Kidney Care Centre provides dialysis services across East and West Kent from a central hub with 5 satellite units. The dialysis service is predominantly nurse led and availability of medical assistance varies considerably between units, in particular the satellite units, depending on their geographical location. Continuing education is currently delivered in skills-based sessions. A learning need was identified by the renal team to include practical training for dialysis staff, to be able to recognise medical emergencies, call for appropriate assistance and initiate management. Renal specific simulation was suggested as a modality to address this. Summary of project: A pilot session was designed and implemented by members of the renal multi-disciplinary team in conjunction with the Trust simulation department. Five scenarios were designed to be managed by two ILS trained, registered nurses with telephone assistance from a renal specialty trainee doctor. The Trust simulation room was adapted to resemble a dialysis unit station. A haemodialysis machine and circuit were modified to allow the participants to interact with the machine, the manikin was modified to have vascular access in the form of a fistula or central venous catheter. A multi-disciplinary faculty consisting of simulation and renal personnel (led by the Renal Nurse Consultant) was recruited. Nine nursing staff from 5 of the units volunteered to attend as participants. Each scenario was followed by a structured debrief with a trained facilitator. Summary of results: Preliminary results from the post-course feedback survey indicate that all participants in the pilot found the course to be 'good' or 'excellent' and would recommend the course. Candidates found the course realistic and commented that they felt it would improve their confidence in dealing with medical emergencies in practice. One candidate specifically mentioned that it would help them to reflect on their clinical practice. Discussion, conclusions and recommendations: The results of our pilot are encouraging with regards to the use of simulation in renal dialysis education, however, our numbers are too small for definitive conclusions to be drawn on its true utility. We intend to roll-out this programme to larger groups, including all levels of renal dialysis staff and core medical trainees, and evaluate their perceptions. We are currently considering whether an in-situ approach would be preferable to deliver this programme. We hope to show a correlation between simulated renal education and a reduction in clinical incidents in the future. Reference: Watson K, Keane O, Sanctuary T, et al . A novel patient safety initiative: Interprofessional in situ simulation for the management of medical emergencies in hospital and community dialysis centres. British Journal of Renal Medicine 2017;22(4):105–08.